UGC Guidelines for Institutional Development Plans for Higher Education Institutions : An Overview - Dr. H. M. Naveen (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The National Education Policy (NEP) 2020, seeks to transform higher education by focusing on skill-based education to meet the needs of the industry and the economy. According to the Institutional Development Plans (IDP) guidelines the Higher Educational Institutions (HEI) have to undertake the Academic and Professional Excellence journey as the heart of these guidelines. The UGC guidelines points out that, in the context of HEIs, governance refer to the systematic approach by which educational institutions are directed, controlled, and held accountable. It encompasses the methods and frameworks utilized for decision-making, risk monitoring, and performance enhancement.
Keywords: Institutional Development Plans; Principles; Objectives and Goals; Strategy Formulations; Higher Education Institutions